Pengaruh Pertumbuhan Perusahaan, Keputusan Pendanaan, Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada PT Sumber Alfaria Trijaya Tbk Periode 2015 - 2024 - Ariansyah, Noval; Supriatna, Agus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to analyze and empirically prove the influence of company growth, financing decisions, and dividend policies on company value at PT Sumber Alfaria Trijaya Tbk (AMRT) for the period 2015-2024. The type of research used is quantitative research with an associative research method approach. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for the period 2015-2024 for 10 years so that the number of data collected is 10 observation data. The data is processed using the Eviews 9 Statistics Program. Company growth is measured using the asset growth ratio formula, financing decisions are measured using the Debt to Equity Ratio (DER) formula, dividend policy is measured using the Dividend Payout Ratio (DPR) formula, and company value is measured using the TobinsQ ratio formula. This study was conducted for 10 months from November 2024 to August 2025. Hypothesis testing in this study uses multiple regression analysis. The results of the t-statistic test show that partially the company's growth does not affect the company's value because the probability of company growth is 0.8212 > 0.05 and the t-statistic result is also obtained at 0.236164 < 2.44691, then the dividend policy does not affect the company's value because the probability of dividend policy is 0.7680 > 0.05 and the t-statistic result is also obtained at 0.308730 < 2.44691, but the funding decision affects the company's value because the probability of funding decision is 0.0082 < 0.05 and the t-statistic result is also obtained at 3.872155 > 2.44691. The results of the F-statistic test show that the company's growth, funding decisions, and dividend policy affect the company's value because the F-statistic is 6.405702 > 3.71 and the F-statistic probability is 0.026697 < 0.05. Keywords: Company Value, company growth, funding decisions, Dividend Policy